Project-Based Virus Enrichment Module Local Issue Context - Sri Handayani; Suranto; Umi Fatmawati (Journal of Education Reseach and Evaluation, 2025)
The characteristics of the independent curriculum include the implementation of project-based learning and local content, but there are still some teachers who have difficulty implementing project-based learning with local content. This study aims to determine the need for a project-based virus enrichment module with a local issue context as additional learning media for students. This study uses quantitative and qualitative descriptive methods with the research subjects being 35 grade X students and one biology teacher. Data collection techniques through questionnaires and interviews. The questionnaire was filled out by a biology teacher and 35 grade X students. Interviews were conducted with a biology educator and four students. Data analysis techniques by describing research data in the form of percentages and opinion descriptions. The results of the needs analysis show that the virus material is considered difficult because it is abstract, learning still uses textbooks and has never been project-based, while students enjoy learning that makes them do activities in a fun way and produce work. They felt the need for additional learning resources besides textbooks, especially virus development material. Therefore, learning media in the form of project-based enrichment modules on viruses in plants needs to be developed to meet the demands of the independent curriculum and improve students' 4C skills in facing the challenges of the 21st century.